PENGARUH UKURAN BANK, PROFITABILITAS, KEPEMILIKAN INSTITUSIONAL, UKURAN DEWAN PENGAWAS SYARIAH DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) - Lestari, Yogi Dwi (Journal of Economics and Policy Studies (JEPS), 2020)
The objective of this study was to measure the extent to which the disclosure of ISR has been applied to Islamic banks (sharia banks), to test and to analyze the factors that affect the disclosure of ISR is bank size, profitability, institutional ownership, size of the sharia supervisory board and age of the company. The data was analyzed by using linear regression of panel data (2016-2019, 10 Banks). According to the results of content analysis, the average disclosure of ISR on Islamic Banks in Indonesia reached 67% or it was adequate. The bank size, the size sharia supervisory board and age of the company had a significantly positive effect to the disclosure of ISR. Institutional ownership had a positive effect not significant to the disclosure of ISR while profitability had no significant effect to the disclosure of ISR.